Comparison of the Effectiveness of Spiritual Therapy and Mindfulness-Based Cognitive Therapy on Social Anxiety in Older Adults with Cardiovascular Disease - Mousavi, Hengameh Sadat; Farokhzad, Pegah; Nabavi Aleagha, Fariba (Iranian Journal of Neurodevelopmental Disorders, 2026)
Purpose: The present study aimed to compare the effectiveness of spiritual therapy and mindfulness-based cognitive therapy on social anxiety in older adults with cardiovascular disease.Methods and Materials: This study employed a quasi-experimental design with a pretest–posttest–follow-up structure including two experimental groups and one control group. The statistical population consisted of older adults aged 65 years and above with cardiovascular disease who were referred to Imam Jafar Sadiq Super-Specialty Hospital in 2021. Using multistage sampling, 45 participants were selected and randomly assigned to spiritual therapy, mindfulness-based cognitive therapy (MBCT), and control groups (15 participants in each group). Data were collected using the Social Anxiety Questionnaire developed by Jerabek (1996). The spiritual therapy intervention was based on the protocol by Boalhari et al. (2012), and the MBCT intervention followed Segal et al. (2009), each delivered in eight 90-minute group sessions. Data were analyzed using repeated-measures multivariate analysis of variance (MANOVA) in SPSS version 27.Findings: The results indicated that the main effect of group on social anxiety components was significant (p < .05), demonstrating differences among the three groups. The within-group effect across time (pretest, posttest, and follow-up) was also significant (p < .05), indicating changes in social anxiety over time. Bonferroni post hoc tests revealed significant differences between pretest and posttest, and between pretest and follow-up in the experimental groups (p < .05), while no significant difference was found between posttest and follow-up (p > .05), indicating stability of treatment effects. The interaction effect of time and group was significant (p < .05), showing differential changes across groups over time. However, no significant difference was found between the spiritual therapy and MBCT groups in overall effectiveness (p > .05).Conclusion: Both spiritual therapy and mindfulness-based cognitive therapy are effective interventions for reducing social anxiety in older adults with cardiovascular disease, and their effects are maintained over time; however, neither approach demonstrates superiority over the other.